2017
DOI: 10.1073/pnas.1715500114
|View full text |Cite
|
Sign up to set email alerts
|

Global biogeochemical cycle of vanadium

Abstract: Synthesizing published data, we provide a quantitative summary of the global biogeochemical cycle of vanadium (V), including both human-derived and natural fluxes. Through mining of V ores (130 × 10 9 g V/y) and extraction and combustion of fossil fuels (600 × 10 9 g V/y), humans are the predominant force in the geochemical cycle of V at Earth's surface. Human emissions of V to the atmosphere are now likely to exceed background emissions by as much as a factor of 1.7, and, presumably, we have altered the depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
142
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(146 citation statements)
references
References 120 publications
1
142
1
2
Order By: Relevance
“…Despite the low particle fraction below 1%, Fe/V-containing particles showed an increase with extinction. Similar to EC2 particle type, vanadium containing particles are good tracers for anthropogenic emissions, in particular oil and coal combustion and production (Schlesinger et al, 2017). Particularly interesting for marine environments, earlier studies showed the presence of the Fe/V particle type to be associated with ship emission (Agrawal et al, 2008;Ault et al, 2010;Coggon et al, 2012).…”
Section: Presence and Properties Of Aerosol And Trace Gases In The Bamentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the low particle fraction below 1%, Fe/V-containing particles showed an increase with extinction. Similar to EC2 particle type, vanadium containing particles are good tracers for anthropogenic emissions, in particular oil and coal combustion and production (Schlesinger et al, 2017). Particularly interesting for marine environments, earlier studies showed the presence of the Fe/V particle type to be associated with ship emission (Agrawal et al, 2008;Ault et al, 2010;Coggon et al, 2012).…”
Section: Presence and Properties Of Aerosol And Trace Gases In The Bamentioning
confidence: 99%
“…The increase of the EC2 type indicates the rather aged character of the plume, and Fe/V might suggest the influence of ship fuel combustion (Agrawal et al, 2008;Ault et al, 2010). Nevertheless, vanadium containing particles are emitted by other industrial activities (Schlesinger et al, 2017) and due to the limited understanding of the chemical speciation of vanadium in primary aerosol sources (Shafer et al, 2012), the direct influence of shipping on this particular extinction event cannot be confirmed.…”
Section: Pollution Events Over the Bornholm Basinmentioning
confidence: 99%
“…Recent studies indicate that the exposure of continental land above sea level is very limited until the middle of the Archean with lower elevation than that of the present-day plateaus (Bada & Korenaga, 2018;Flament, Coltice, & Rey, 2013;Korenaga, Planavsky, & Evans, 2017), thus possibly constraining the input of continental weathering of vanadium to the shallow ocean. Additionally, pervasive hydrothermal flux of Fe (Kump & Seyfried, 2005) and massive precipitation of iron (hydr)oxides as banded iron formations (BIFs; Klein, 2005) further limited the availability of vanadium in early seawater as surface adsorption or coprecipitation of vanadium along with iron (hydr)oxides and clay minerals are major sinks of the modern vanadium cycle (Breit & Wanty, 1991;Huang et al, 2015;Schlesinger, Klein, & Vengosh, 2017), and presumably in the Archean. Therefore, before the prominent occurrence and elevation of continental lands in the mid-Archean, limited weathering supply and large adsorption/coprecipitation sinks would have resulted in low concentrations of vanadium in the oceans, as evidenced by low V concentrations in early Archean BIFs (Aoki, Kabashima, Kato, Hirata, & Komiya, 2018).…”
Section: Evolving Vanadium Redox State and Availabilitymentioning
confidence: 99%
“…These piles were stored outdoors in a densely populated community of color that has experienced a long history of environmental racism, including an ongoing concern with heavy metal contamination from steel mills (Hawthorne, ). Unconventional fossil fuels, like petcoke, are substantial contributors to heavy metal contamination (Schlesinger, Klein, & Vengosh, ). In the clarification statement of HS‐ESS3‐2, and in the “nature of science” appendix, the NGSS argue that “Science knowledge indicates what can happen in natural systems—not what should happen.” But this statement artificially disentangles natural, social, and political systems within the HS‐ESS3‐2 context of mining for minerals in ways that are contradicted by the standards’ own suggestions to engage students with neoliberal framings of gold mining, oil drilling, and the best practices for exploiting unconventional fossil fuels.…”
Section: Harms and Chemistry Educationmentioning
confidence: 99%
“…These piles were stored outdoors in a densely populated community of color that has experienced a long history of environmental racism, including an ongoing concern with heavy metal contamination from steel mills (Hawthorne, 2018). Unconventional fossil fuels, like petcoke, are substantial contributors to heavy metal contamination (Schlesinger, Klein, & Vengosh, 2017). In the clarification statement of HS-ESS3-2, and in the "nature of science" appendix, the NGSS argue that "Science knowledge indicates what can happen in natural systems-not what should happen."…”
mentioning
confidence: 99%